Eristalinus arvorum (Fabricius, 1787) (Diptera: Syrphidae) in Human Skull: A New Fly Species of Forensic Importance. Issue 1 (15th July 2019) - Heo, Chong Chin; Rahimi, Razuin; Mengual, Ximo; M. Isa, Mohd. Shahirul; Zainal, Syameem; Khofar, Putri Nabihah; Nazni, Wasi Ahmad
Abstract: A body of an unknown adult female was found within a shallow burial ground in Malaysia whereas the skull was exposed and visible on the ground. During autopsy examination, nine insect larvae were recovered from the interior of the human skull and subsequently preserved in 70% ethanol. The larvae were greyish in appearance, each with a posterior elongated breathing tube. A week after the autopsy, more larvae were collected at the burial site, and some of them were reared into adults. Adult specimens and larvae from the skull and from the burial site were sequenced to obtain DNA barcodes. Results showed all adult flies reared from the burial site, as well as the larvae collected from the skull were identified as Eristalinus arvorum (Fabricius, 1787) (Diptera: Syrphidae). Here, we report the colonization of E. arvorum larvae on a human corpse for the first time.